PepO and CppA modulate Streptococcus sanguinis susceptibility to complement immunity and virulence - Alves, Lívia A.; Naveed, Hassan; Franco, Eduardo M.; Garcia, Maíra Terra [UNESP]; Freitas, Victor A.; Junqueira, Juliana C. [UNESP]; Bastos, Débora C.; Araujo, Thaís L. S.; Chen, Tsute; Mattos-Graner, Renata O. (Taylor & Francis, 2023)
Streptococcus sanguinis is a ubiquitous commensal species of the oral cavity commonly involved as an opportunistic pathogen in cardiovascular infections. In this study, we investigated the functions of endopeptidase O (PepO) and a C3-degrading protease (CppA) in the systemic virulence of S. sanguinis. Isogenic mutants of pepO and cppA obtained in strain SK36 showed increased susceptibility to C3b deposition and to opsonophagocytosis by human polymorphonuclear neutrophils (PMN). These mutants differ, however, in their profiles of binding to serum amyloid P component (SAP) and C1q, whereas both showed reduced interaction with C4b-binding protein (C4BP) and/or factor H (FH) regulators as compared to SK36. The two mutants showed defects in ex vivo persistence in human blood, serum-mediated invasion of HCAEC endothelial cells, and virulence in a Galleria mellonella infection model. The transcriptional activities of pepO and cppA, assessed by RT-qPCR in nine wild-type strains, further indicated strain-specific profiles of pepO/cppA expression. Moreover, non-conserved amino acid substitutions were detected among the strains, mostly in CppA. Phylogenetic comparisons with homologues of streptococcal species of the oral and oropharyngeal sites suggested that S. sanguinis PepO and CppA have independent ancestralities. Thus, this study showed that PepO and CppA are complement evasion proteins expressed by S. sanguinis in a strain-specific manner, which are required for multiple functions associated with cardiovascular virulence.
Keywords: cardiovascular diseases; complement system; endothelial cell; Galleria mellonela; peptidase; Streptococcus sanguinis